Firm productivity, heterogeneity and macroeconomic dynamics: A data-driven investigation - Mihnea Constantinescu; Aurelija Proškutė (Baltic Journal of Economics, 2019)
In this paper, we offer a unique firm-level view of the empirical regularities underlying the evolution of the Lithuanian economy over the period of 2000-2014. Employing a novel dataset, we investigate key distributional moments of real and financial variables of Lithuanian firms. We focus in particular on the issues related to productivity, firm birth and death and the associated employment creation and destruction across firm sizes, industry classification and trade status (exporting vs. non-exporting). We refrain from any structural modelling attempt in order to map out the key economic processes across industries and selected firm characteristics. Nevertheless, existing theoretical and empirical findings guide our analysis and the selection of the main variables to investigate. We uncover similar regularities as already highlighted in the literature: trade participation and firm productivity are strongly positively linked, the 2008 recession has had a cleansing effect on the non-tradable sector, firm birth (death) is highly pro(counter)-cyclical. The richness of the dataset allows us to produce additional insights: for example, we observe an increasing share of exporting but a constant share of importing firms since 2000.
Keywords: D22; D24; E30; J21; J24; J30; L11; L25; 330; firm dynamism; firm heterogeneity; job creation and destruction; Lithuanian economy; Productivity